Strategi Membangun Citra Produk Hello Bubble dalam Komunitas The Crew melalui Brand Ambassador Blackpink - Shanice, Elaine; Pandrianto, Nigar (Kiwari, 2024)
With the presence of technology, it creates very free and broad opportunities for globalization. Freely and widely, other cultures enter and interact with the original culture. One of them is the Korean Wave culture or what is more often called K-Wave. Now the Korean Wave is not just about music, but about the culture of fashion, makeup, drama, food and others. Blackpink itself is a girl group that is known globally thanks to its many achievements in their career. Blackpink is believed to be the brand ambassador for Hello Bubble hair coloring products. "THE CREW" is a community formed by the Indonesian mise en scene team which operates around haircare and hair products. The “THE CREW” community was formed with the aim of being a forum for hair product enthusiasts to exchange ideas. This research aims to determine Blackpink's role as brand ambassadors in building an image within the "THE CREW" community. This research is research with a qualitative approach and case study method. The results of this research show that Blackpink plays a very important role in creating the image of the Hello Bubble product among members of the "THE CREW" community. Dengan hadirnya teknologi, menciptakan kesempatan yang sangat bebas dan luas untuk globalisasi. Secara bebas dan luas kebudayaan-kebudayaan lain masuk dan berinteraksi dengan kebudayaan asli. Salah satunya yaitu dengan kebudayaan Korean Wave atau yang lebih sering disebut K-Wave. Kini Korean Wave bukan hanya mengenai musik saja, melainkan mengenai budaya fashion, makeup, drama, makanan, dan lainnya. Blackpink sendiri salah satu girl group yang dikenal secara global berkat segudang prestasi dalam karier mereka. Blackpink dipercaya menjadi brand ambassador dari produk pewarna rambut Hello Bubble. “THE CREW” merupakan komunitas yang dibentuk oleh tim mise en scene Indonesia yang bergerak seputar haircare dan hair products. Komunitas “THE CREW” dibentuk dengan tujuan untuk menjadi wadah bagi para penyuka produk rambut untuk bertukar pikiran. Penelitian ini bertujuan untuk mengetahui peran Blackpink sebagai brand ambassador dalam membangun citra di dalam komunitas “THE CREW”. Penelitian ini menggunakan pendekatan kualitatif dan metode studi kasus. Hasil penelitian ini menunjukkan bahwa Blackpink sangat berperan dalam menciptakan citra dari produk Hello Bubble di anggota komunitas “THE CREW”.